A temporal message ordering and object tracking application - Lakshman, Kaveti (Kansas State University, 2008)
TinyOS is an operating system designed for wireless embedded sensor network which supports the component based development language called Nesc. Wireless sensor network are becoming increasingly popular and are being used in various applications including surveillance applications related to object tracking. Wireless sensor devices called motes can generate an event in the network whenever there is some object moving in its vicinity. This project aims to develop an application which detects the path information of object moving in the sensor field by capturing the order of events occurs in the network. This application builds a logical topology called DAG (Directed acyclic graph) between the motes in the network which is similar to the tree topology where a child can have multiple parents which are in communication range and a level closer to the root. Using a DAG, motes can communicate efficiently to order the events occurring in the sensor field. The root of the DAG is the base station which receives all the events occurred in the network and orders them based on the information it has from previous events received. Every event occurring in the network is assigned a time stamp and is identified by a tuple (mote_id, timestamp) which describes that the mote with identity id has detected the object with the timestamp, and ordering all such events based on the timestamps we get the path information. There are two time stamping algorithms written in this project. In the first time stamping algorithm, whenever any event occurs, it updates the timestamp information of the entire neighboring mote in the field and when the object enters in the detection range of neighboring mote of previous detected mote, it assigns the new timestamp. The second time stamping algorithm just send the message to the parent and it passes on to its parent until the message is received at the base station, and base station itself assigns the timestamps based the event on first come first serve basis. The application is tested by displaying the path information received and ordered at the base station.
Keywords: Message; Ordering; Object; Tracking; Computer Science (0984)